The Place and Role of Tourist Companies in the Organization of Tourist Trips - Toychievna, Alieva Makhbuba; Jonibek, Kodirov (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information about the place and role of tourist companies in the organization of tourist trips.